Fish Value Addition and Livelihood Outcomes of Fishing Communities: Evidence from Mkinga District, Tanzania: Fish Value Addition and Livelihood Outcomes - Abeid Hussein Rashid (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2026)
Fish value addition has been widely recognised as a catalyst for improving the livelihoods of fishing communities in sub-Saharan Africa. However, empirical evidence on its structural, economic, and socio-livelihood implications within specific coastal districts of Tanzania remains sparse. Objective: This study investigates the implications of fish value addition on the livelihood outcomes of fishing communities in Mkinga District, Tanga Region, Tanzania. Methods: A cross-sectional design was employed. Data were collected from 338 randomly selected registered fishermen using structured questionnaires, supplemented by semi-structured interviews, focus group discussions, and documentary analysis. Value chain mapping, descriptive statistics, and financial profitability analysis were applied. Results: The fishing value chain in Mkinga comprises eight distinct strands involving fishers, assemblers, wholesalers, processors, retailers, food vendors, and consumers. Fishermen demonstrated high awareness of value addition benefits (99.1% affirmed income-enhancement potential), yet practical adoption remains severely constrained by limited access to processing equipment (8.7% reported access), high initial costs (98.3%), and market barriers (93.0%). Average daily fish revenue stood at TZS 83,904 (approximately USD 32), with processed fish strands achieving up to TZS 9,000 per kilogram compared to TZS 3,983 for fresh fish. Housing conditions are predominantly rudimentary, 53.9% of households face regular food insecurity, and all respondents rely exclusively on uncovered wells for drinking water. Conclusion: Value addition holds transformative potential for coastal fishing communities in Mkinga but remains constrained by structural gaps in infrastructure, finance, and market access. Targeted policy interventions involving cooperative strengthening, processing technology subsidies, and market information systems are urgently needed.